If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.75(16 + -12x) + -8x = -22 (16 * 0.75 + -12x * 0.75) + -8x = -22 (12 + -9x) + -8x = -22 Combine like terms: -9x + -8x = -17x 12 + -17x = -22 Solving 12 + -17x = -22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -17x = -22 + -12 Combine like terms: 12 + -12 = 0 0 + -17x = -22 + -12 -17x = -22 + -12 Combine like terms: -22 + -12 = -34 -17x = -34 Divide each side by '-17'. x = 2 Simplifying x = 2
| 0=(4x+1)(x-8) | | 5y-4=11y+14 | | x^2+4x-260=0 | | 8-6p-7p=31 | | 3x+3y+6=36 | | 16x-15=2x-8 | | 5z-3=z+9 | | 2=s+18 | | x^2-9x+2=36 | | 9x-5=21+3 | | 2-9t=0 | | m-39=-11 | | 7r^2-4r+7=0 | | y=-3(3)+5 | | 40a^3+5b^3= | | -3y-15=45 | | 7x+3(x-2)=6(x+1)-3 | | 2(k+5)-3=k+18 | | Y=-3(-6)+5 | | 6x^2-2=135 | | 7x-2=7(x+4) | | 5wk-3k-6k+k-10= | | 7x+8-6x=3 | | -4+2y=3y-6 | | 22-10n+n^2=-2 | | -7m+13+8m-5= | | 7=3z+2 | | 7x+8-6x+3= | | 2y-6=11y+57 | | -22x-1x= | | (x+5)(x-9)=(2x+7)(x-5) | | ax-b=4x-7 |